2021
DOI: 10.5812/ijem.109285
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Indices and Age at Natural Menopause: A 15-Year Follow-up Population-Based Study

Abstract: Background: Following menopause, the risk of many diseases is increased, and this situation may be due to changes in anthropometric indices (AI), while the association between adiposity and age at natural menopause (ANM) is not clear yet. Objectives: This longitudinal study was conducted to investigate the ability of AI in predicting ANM. Methods: For this purpose, a total of 3,876 women aged > 20 years old from participants of the Tehran lipid and glucose study (TLGS) met our eligibility criteria. The asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…In Canada, obesity (BMI, >30 kg/m 2 ) was also associated with later natural menopause (HR, 0.89; 95% CI, 0.82-0.96), whereas no association was identified for underweight (BMI, <20 kg/m 2 ) 12 . A recent prospective study showed that the median time until natural menopause increased by about 1% with an increase of one SD in the BMI z score of Iranian women over 15 years of follow-up 56 . The link between excess weight and age at natural menopause may be explained by the complex functions of adipose tissue and its metabolism, including the androstenedione conversion into estrone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Canada, obesity (BMI, >30 kg/m 2 ) was also associated with later natural menopause (HR, 0.89; 95% CI, 0.82-0.96), whereas no association was identified for underweight (BMI, <20 kg/m 2 ) 12 . A recent prospective study showed that the median time until natural menopause increased by about 1% with an increase of one SD in the BMI z score of Iranian women over 15 years of follow-up 56 . The link between excess weight and age at natural menopause may be explained by the complex functions of adipose tissue and its metabolism, including the androstenedione conversion into estrone.…”
Section: Discussionmentioning
confidence: 98%
“…12 A recent prospective study showed that the median time until natural menopause increased by about 1% with an increase of one SD in the BMI z score of Iranian women over 15 years of follow-up. 56 The link between excess weight and age at natural menopause may be explained by the complex functions of adipose tissue and its metabolism, including the androstenedione conversion into estrone. 57,58 Additionally, a high concentration of free estrogen, resulting from the reduction or suppression of sex hormone-binding globulin induced by adiposity, may contribute to delaying the onset of menopause.…”
Section: Age At Natural Menopause In Brazilian Womenmentioning
confidence: 99%
“…During post-menopause, women may experience serum lipid changes [ 8 ] via the redistribution of the fat mass to the abdominal compartment, reducing activity, energy expenditure, and fat oxidation, thus modifying their body composition via the augmentation of fat mass and diminishing muscle mass [ 9 ]. These disturbances in lipid metabolism and anthropometric condition along with an imbalance in antioxidant status increase the risk of impaired cardiovascular and oxidative stress-related parameters as menopause advances [ 10 ].…”
Section: Introductionmentioning
confidence: 99%